2002
DOI: 10.1111/j.0006-341x.2002.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimators of Tissue Proportions from X-Ray CT Images

Abstract: Estimators are derived of tissue proportions from X-ray computed tomography (CT) images. These take into account that many pixels in such images are responses to mixtures of tissue types. The problem is motivated by an application involving estimation of sheep tissue weights. The standard estimator, a count of the number of pixels in a particular range of values, is compared with the maximum likelihood fit of a mixed-pixel distribution and a moment-based estimator. Both simulations and the application show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Focusing on the muscle -fat density range, pure tissues of either type have only a narrow range of pixel values and many of the pixels can be characterised as mixed pixels (Choi et al, 1991). The possible classification methods were evaluated by Glasbey and Robinson (2002).…”
mentioning
confidence: 99%
“…Focusing on the muscle -fat density range, pure tissues of either type have only a narrow range of pixel values and many of the pixels can be characterised as mixed pixels (Choi et al, 1991). The possible classification methods were evaluated by Glasbey and Robinson (2002).…”
mentioning
confidence: 99%
“…A highly sophisticated approach to pixel classification has been described 6 . This recognizes “mixed pixels,” i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work has been carried out in dogs, 3 poultry, 4 pigs, 5 and sheep 6 using CT in body composition studies. This aspect of imaging and the wide range of approaches to the topic in humans have been reviewed, 7 and automated computer-aided approaches, especially for the determination of adipose volumes, have been described for MR images [8][9][10] and CT 11,6 in various species. This paper describes the details of a program written in the ImageJ macro language 12 for the automated measurement of subcutaneous adipose tissue thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The range of 210 to þ93 Hu was used in this study. A more sophisticated approach is to take account of mixed pixels, as in Glasbey and Robinson (2002), though in practice the authors found that the differences in estimated areas were very small.…”
Section: Figurementioning
confidence: 99%